Pathogenic and therapeutic roles of extracellular vesicles in sepsis - Benshuai You; Yang Yang; Jing Wei; Chenglin Zhou; Surong Dong (Frontiers in Immunology)
Sepsis is a systemic injury resulting in vascular dysfunction, which can lead to multiple organ dysfunction, even shock and death. Extracellular vesicles (EVs) released by mammalian cells and bacteria have been shown to play important roles in intercellular communication and progression of various diseases. In past decades, the functional role of EVs in sepsis and its complications has been well explored. EVs are one of the paracrine components of cells. By delivering bioactive materials, EVs can promote immune responses, particularly the development of inflammation. In addition, EVs can serve as beneficial tools for delivering therapeutic cargos. In this review, we discuss the dual role of EVs in the progression and treatment of sepsis, exploring their intricate involvement in both inflammation and tissue repair processes. Specifically, the remarkable role of engineered strategies based on EVs in the treatment of sepsis is highlighted. The engineering EVs-mediated drug delivery and release strategies offer broad prospects for the effective treatment of sepsis. EVs-based approaches provide a novel avenue for diagnosing sepsis and offer opportunities for more precise intervention.